Novel First Order Current Mode MOS-C Phase Shifters - ÖZENLİ, DENİZ (KAUNAS UNIV TECHNOLOGY, 2018)
In this work, novel first order MOS-C phase shifter structures are proposed in NMOS and PMOS configurations. Core circuits consist of only three transistors and a single capacitor. The pole frequency of the phase shifters can be easily controlled by the bias voltage. The presented circuits in this work bring advantages such as low power consumption and small chip area when compared to other works including large numbers of active and passive elements in the literature. Furthermore, the proposed circuits are designed with a simple design automation flow that is proper for MOS-Only or MOS-C architectures. It is shown by simulations that the simulation results agree with the theoretical results for a wide frequency range.
Keywords: All-pass; Current mode; Phase shifter; MOS-Only; MOS-C; Polynomial regression; Design automation; ALL-PASS FILTER